The Effectiveness of English Dialogue Study for Agricultural Business Students in the Language Laboratory at Pangkep State Agricultural Polytechnic - Yusri Muhammad Yusuf (Citakonsultindo, 2023)
Learning the English language is not easy, but it is also not as difficult as turning one's hand. What matters is willingness and perseverance. The aim of this research is to enable students to learn English easily and quickly. The method employed in this study is experimental (action research). The analysis utilized involves processing the data obtained in this research through scoring, assigning a score of ten to each word eliminated in the dialogue. The total number of words eliminated in the dialogue is ten. The results of English Language Teaching at Pangkep State Agricultural Polytechnic are still considered a challenging subject for students, encompassing aspects of content, methodology, and the evaluation tools used to assess their mastery of the taught material.